Novel Types of Hypermodified Fluorescent Phyllobilins from Breakdown of Chlorophyll in Senescent Leaves of Grapevine (Vitis vinifera). Issue 65 (30th October 2018) - Erhart, Theresia; Mittelberger, Cecilia; Liu, Xiujun; Podewitz, Maren; Li, Chengjie; Scherzer, Gerhard; Stoll, Gertrud; Valls, Josep; Robatscher, Peter; Liedl, Klaus R.; Oberhuber, Michael; Kräutler, Bernhard
Abstract: The tetrapyrrolic chlorophyll catabolites (or phyllobilins, PBs) were analyzed in yellow fall leaves of the grape Chardonnay, a common Vitis vinifera white wine cultivar. The major fractions in leaf extracts of V. vinifera, tentatively assigned to PBs, were isolated and their structures elucidated. The dominant fraction is a dioxobilin‐type non‐fluorescent Chl‐catabolite of a previously observed type. Two less polar fluorescent PBs were characterized as a novel dioxobilin‐type fluorescent Chl‐catabolite with a bicyclo‐1′, 6′‐glycosyl architecture, and its new fluorescent formyloxobilin‐type analogue. The discovery of persistent hypermodified fluorescent PBs with the architecture of bicyclo‐[17.3.1]‐PBs ( bc PBs), suggests the activity of an unknown enzyme that forges the 20‐membered macroring at the tetrapyrrolic core of a fluorescent PB. bc PBs may play specific physiological roles in grapevine plants and represent endogenous anti‐infective agents, as found similarly for other organic bicyclo‐[ n .3.1]‐1′, 6′‐glycosyl derivatives. Abstract : The colors of the fall : Blue fluorescent chlorophyll catabolites with a unique bicyclo‐1′, 6′‐glycosyl architecture occur in golden yellow fall leaves of Chardonnay, a common white wine cultivar. This discovery implies unknown enzymes that assemble a 20‐membered macroring at a tetrapyrrole to generate exceptionally structured chlorophyll catabolites. Possibly, these may play specific physiological roles and/or represent anti‐infective agents in the grapevine leaves.